(untitled) (American & British Studies Annual, 2010)
Immigration is a frequent theme in American literature both in fiction and in so-called ego-documents. But while United States was often considered a country of immigrants, immigration has only lately ceased to be automatically linked with assimilation and integration. In my analysis of the Julia Alvarez’s novel How the García Girls Lost Their Accents (1991), I will focus on how immigration is depicted as both a loss and a gain, as a kind of oscillation between the need to accommodate to new home and to retain what is fundamental to one’s identity from the old.